Evaluation of Road Performance under the Influence of Volunteer Traffic Regulators (Supeltas): A Case Study in Pekanbaru - Surya Abdillah Zebua (MSD Institute, 2025)
Traffic congestion remains a major challenge in Indonesian cities, where limited enforcement capacity has led to the emergence of Volunteer Traffic Regulators (Supeltas) as community-based traffic managers. This study evaluates the impact of Supeltas on traffic performance at a U-turn on Jl. Soekarno Hatta, Pekanbaru City. A mixed-method approach combining qualitative observation and quantitative road performance analysis was employed, following the Indonesian Road Capacity Guidelines (PKJI) and U-turn Planning Guidelines (PPPB). Traffic data were collected over two weeks under conditions with and without Supeltas. The results show that Supeltas increase vehicle volume at the U-turn (from 2,131 to 2,168 pcu/hour) but also reduce average speed (from 42 km/h to 37 km/h) and raise the degree of saturation from 0.36 to 0.49, shifting the Level of Service from B to C. These findings indicate that while Supeltas help manage driver behavior and encourage U-turn utilization, their presence also contributes to higher congestion levels due to inconsistent manual signaling. Improved Supeltas training and dedicated U-turn lanes are recommended to enhance operational efficiency and safety.